Air transportation and regional growth: which way does the causality run? - Kirsi Mukkala; Hannu Tervo (European Regional Science Association (ERSA), 2012)
The role of airports has become increasingly important with globalization. To have a regional airport is an especially important asset for retaining companies in the region as well as attracting new economic activity to the region. A well-developed transport infrastructure can be seen as a facilitator that allows the economic potential of a region to be realized. The provision of transportation does not, however, automatically lead to economic growth. It may also be the other way round: economic development leads to the better transport infrastructure and accessibility, stressing demand side elements. This paper aims to shed further light on the relationship between regional airports and economic performance. We ask whether accessibility is a key factor to economic success, or rather a consequence of it. In order to test the relative importance of various effects, the Granger non-causality method in a panel framework is applied. The Granger method exploits the fact that in time series there is temporal ordering, and the belief that effects cannot occur before causes. The empirical analysis is based on European level annual data from 86 regions and 13 countries on air traffic and regional economic performance in the period 1991-2010. The results revealed that for at least some regions (and possible all), there is statistical evidence of Granger causality from air traffic to regional growth but these processes are not uniform in all regions. The categorization of the regions into three groups of equal size according to their peripherality showed significant causality in peripheral regions and indicative causality in intermediate regions, while in core regions no significant causality was found. Hence, peripherality indeed matters: the more remote the region is the more important for it is to have efficient air connections. The evidence of the opposite direction of causality - from regional development to air traffic - was only partial and homogenous.
Keywords: 330; air traffic; regional growth; Granger causality